Mechanical property study on C90300 copper composites reinforced with rare earth oxide. (2020) - Mayilsamy, P.; Kumareshbabu, S.P.; Nayan, Kamal; Srinivasan, S.A.
Abstract: The copper alloys with conventional grain structure and size are soft materials with relatively low yield strength. The strength of copper based CMCs increases with the reinforcement addition. In the present experiment we have gone with Tin bronze as the matrix, an alloy of copper since it has got superior properties compared to copper due to the incorporation of Tin. The experiment revolves around the development of composite of Tin bronze with Rare Earth Oxide addition. Addition of Rare Earth Metal results in grain refinement and thus helps in increasing the mechanical properties of the material. The Tin Bronze C90300 with 1%, 2%, 3%, 4% and 5% cerium oxide weight percentage were cast. The composites were characterized by X-ray diffraction, Optical microscopy and Scanning Electron Microscopy. The composites were also sent for chemical analysis to adjudge its chemical composition. The effect of rare earth oxide addition on the mechanical properties were investigated by Rockwell hardness test and tensile test. The results showed that addition of cerium resulted in the microstructure refinement and formation of intermetallic phases, which causes pinning effect at the boundaries and increases the hardness and tensile strength of the cast sample.